2007
DOI: 10.1152/jn.00824.2007
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal From Intermittent Ethanol Exposure Increases Probability of Burst Firing in VTA Neurons In Vitro

Abstract: Changing the activity of ventral tegmental area (VTA) dopamine neurons from pacemaker to burst firing is hypothesized to increase the salience of stimuli, such as an unexpected reward, and likely contributes to withdrawal-associated drug-seeking behavior. Accordingly, pharmacological, behavioral, and electrophysiological data suggest an important role of the VTA in mediating alcohol-dependent behaviors. However, the effects of repeated ethanol exposure on VTA dopamine neuron ion channel function are poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 82 publications
6
104
1
Order By: Relevance
“…Recent studies report either no change (Trantham-Davidson et al, 2014) or an increase (Pleil et al, 2015) in AP firing in prelimbic mPFC pyramidal neurons from CIE-exposed rats and mice, respectively. Increases in neuronal excitability following chronic exposure to ethanol have also been reported in other brain areas, including the VTA (Hopf et al, 2007), nucleus accumbens (Hopf et al, 2010), hippocampus (Mulholland et al, 2011), dorsal raphe (Lowery-Gionta et al, 2014), and ventral BNST (Pleil et al, 2015). Several of these studies also reported decreases in SK channel function (Hopf et al, 2007(Hopf et al, , 2010Mulholland et al, 2011;Padula et al, 2015), suggesting that these channels are particularly sensitive to chronic ethanol exposure.…”
Section: Cie Increases Neuronal Excitability Of Lofc Neurons and Redumentioning
confidence: 81%
See 1 more Smart Citation
“…Recent studies report either no change (Trantham-Davidson et al, 2014) or an increase (Pleil et al, 2015) in AP firing in prelimbic mPFC pyramidal neurons from CIE-exposed rats and mice, respectively. Increases in neuronal excitability following chronic exposure to ethanol have also been reported in other brain areas, including the VTA (Hopf et al, 2007), nucleus accumbens (Hopf et al, 2010), hippocampus (Mulholland et al, 2011), dorsal raphe (Lowery-Gionta et al, 2014), and ventral BNST (Pleil et al, 2015). Several of these studies also reported decreases in SK channel function (Hopf et al, 2007(Hopf et al, , 2010Mulholland et al, 2011;Padula et al, 2015), suggesting that these channels are particularly sensitive to chronic ethanol exposure.…”
Section: Cie Increases Neuronal Excitability Of Lofc Neurons and Redumentioning
confidence: 81%
“…Increases in neuronal excitability following chronic exposure to ethanol have also been reported in other brain areas, including the VTA (Hopf et al, 2007), nucleus accumbens (Hopf et al, 2010), hippocampus (Mulholland et al, 2011), dorsal raphe (Lowery-Gionta et al, 2014), and ventral BNST (Pleil et al, 2015). Several of these studies also reported decreases in SK channel function (Hopf et al, 2007(Hopf et al, , 2010Mulholland et al, 2011;Padula et al, 2015), suggesting that these channels are particularly sensitive to chronic ethanol exposure. Although downregulation of SK channel function would be expected to alter AP firing, AHPs are also generated by KCNQ channels that mediate M-currents and HCN channels that underlie the I H current (Gu et al, 2005;Hansen et al, 2008).…”
Section: Cie Increases Neuronal Excitability Of Lofc Neurons and Redumentioning
confidence: 81%
“…Recent work has identified SK-type (small conductance) calcium-activated potassium channels (SK) as a novel therapeutic intervention for alcoholism (Hopf et al, 2007(Hopf et al, , 2010a(Hopf et al, , 2011Mulholland et al, 2010). Long-term alcohol intake, either operant or under intermittent-access twobottle choice, is associated with reduced SK function in the Nacc core but not Nacc shell or dorsal striatum (Hopf et al, 2010a(Hopf et al, , 2011.…”
Section: Sk-type Calcium-activated Potassium Channelsmentioning
confidence: 99%
“…The reason for this change still remains to be determined, however a recent study (Hopf et al, 2007) demonstrated that VTA neurons exhibit increased NMDA-induced bursting during ethanol withdrawal, suggesting that the alteration in DAT expression could be a homeostatic change in response to increasing amounts of dopamine released. Interestingly, we found that DAT levels in the nucleus accumbens were decreased following chronic continuous ethanol exposure.…”
Section: Nucleus Accumbensmentioning
confidence: 99%
“…Currently less is known of the participation of dopamine in chronic actions of ethanol, or conversely, what effects chronic ethanol exposure has on dopaminergic systems. Chronic ethanol exposure has been reported to alter dopaminergic function via modulation of the activity of VTA dopaminergic cells (Brodie, 2002;Shen, 2003;Hopf et al, 2007). In addition to somatic effects on dopaminergic neurons, a number of studies have suggested that chronic ethanol administration can alter dopaminergic function at the level of the dopamine synapse (Casu et al, 2002;Budygin et al, 2003;Budygin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%